The restorative effects of working individually in a vegetated office space: A crossover controlled experimental study in real-life workplace setting. - Zhang, Gaochao; Li, Tingting; Cui, Yu; Ren, Tori Hui (Work, 2025)
Background: Examining the restorative effects of indoor nature exposure that can be controlled through management and design in work settings is crucial for public health. However, concerns about the external validity of existing findings persist due to insufficiency of studies with ecologically sound experimental designs. Objective: Through an experiment that prioritized higher ecological validity, this study aimed to explore the effects of working in an office room vegetated with green plants on employees' physiological and psychological well-being, and their attentional performance. Methods: This controlled experimental study employed a crossover design in real-life work environments, involving 40 working individuals. It assessed changes in perceived fatigue, psychological and physiological stress, and attentional performance after individual work in either a vegetated or plant-free office room, with other environmental factors kept constant. Results: After an hour of individual work in a vegetated room, participants reported decreased perceived stress and fatigue, supported by changes in measures of systolic blood pressure and heart rates when compared to a plant-free room. Gender differences emerged, with females experiencing greater relief in perceived stress and males showing more noticeable reductions in stress-related physiological indicators. Enhanced attentional reactions were noted solely among males. Conclusions: This study accentuated the immediate emotional well-being benefits of indoor plants at work, highlighting the importance of considering diverse user groups in indoor workspace design. It also proposes potential explanations for how indoor plants induce restorative effects on working individuals, suggesting further research.